FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA STIE YKPN DALAM MENGGUNAKAN QUICK RESPONSE CODE INDONESIA STANDARD (QRIS) - Rosita Arini Setyaningsih, Prima; Anastasia Imelda Putri (Jurnal Ekonomi Dan Bisnis, 2024)
This study aims to determine the effect of perceived usefulness, perceived ease of use, and trust on interest in using QRIS. This study was conducted on students at STIE YKPN Yogyakarta. The method used in this study is quantitative, data collection by distributing questionnaires with a total of 130 respondents, and the sampling technique using purposive sampling. Data analysis using multiple regression which was previously tested for data quality, namely validity and reliability tests. The results of this study indicate that perceived usefulness and trust have a positive effect on interest in using QRIS. While perceived ease of use does not affect interest in using QRIS